A practical guide to analysing online support forums - Smedley, Richard; Coulson, Neil S. (Taylor and Francis, 2018)
As the number of online support forums continues to grow and the amount of user-generated content increases, analysing forum messages can provide researchers and others working in health-related fields with important new insights into the needs, opinions and experiences of individuals who use them. There has been a lack of guidance regarding how to make the best use of user-generated content within forums as a data source in research studies, so this paper explains the practical, ethical and methodological issues associated with this type of research. It describes the benefits of forum research, the organisational structure of forums, how forums are selected for research, approaches to sampling, preparing data for analysis, and methods of analysis that can be used. The decisions that researchers need to make during each stage of the research process are explained, describing the options available and the ethical dilemmas that need to be considered to successfully develop, carry out and complete a research project.